Translation Technique and Acceptability of Fantasy Terms from Indonesian to English in Cinderella’s Story - Kammer Tuahman Sipayung; Cristanti Manullang; Winter Anaria Purba; Gita Moriska Sitanggang; Ayu Pardede (Politeknik Negeri Padang, 2022)
Fantasy terms is cultural language which can be a great problems for the translation accepatbility. The aims of this study to find out the translation techniques used by the translator in translating the fantasy terms in Cinderella’s story and to describe the translation acceptability of fantasy terms. To achieve the aims of this study, the researcher used qualitative research design. The instruments of collecting data used by the researchers were interview sheet and translation quality indicator. The source of data are from Cinderella’s Story written and translated by Gibran Maulana and inter-raters. The data of this research are pairs of translation and score of translation accepatbility. The raters on this study are professional translator with education background is linguistics. The study shown that translator apply literal translation techniques (30%) and calque (30%), establish equivalent (10%), discursive creation (10%), reduction (10%), and generalization (10%). The accuracy translation which categorized accurate is 70%, less acceptable is 20% and unaccaptable is 10%. It concludes that translation techniques which are used by the translator categorized good for translating cultural language in cinderella story.